2011
DOI: 10.3109/10428194.2011.574761
|View full text |Cite
|
Sign up to set email alerts
|

CD30: an important new target in hematologic malignancies

Abstract: CD30 is abundantly and selectively expressed on the surface of Hodgkin Reed-Sternberg cells, anaplastic large cell lymphomas (ALCLs), and other lymphoid malignancies as well as on several non-lymphoid malignancies including selected germ cell tumors. Expression of CD30 on normal cells is highly restricted, thereby allowing differential targeting of malignant cells. CD30, a member of the tumor necrosis factor (TNF)-receptor family has pleiotropic biologic functions, and antibodies targeting CD30 and other TNF f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 108 publications
(108 reference statements)
0
63
0
Order By: Relevance
“…Nadali et al stated that CD30 is also detected on non-lymphoid germ cells neoplasms, and can be found sometimes in mesenchymal tumors and nasopharyngeal carcinoma [21,22]. For serum sCD30 levels, high levels have been reported in different neoplasms (HL, ALCL, nasopharyngeal carcinoma, embryonal carcinoma of the testis) characterized by strong T-cell or B-cell activation [23]. In this study we reported that there was a significant correlation between both high CD30 expression and elevated sCD30 and WBCs count, BM blasts, adverse risk cytogenetics, FLT3/ITD mutation (That in contrast to Zheng W et al that found that CD30 expression did not associate with NPM1, FLT3 ITD, D835, or RAS mutation state [24].…”
Section: Discussionmentioning
confidence: 99%
“…Nadali et al stated that CD30 is also detected on non-lymphoid germ cells neoplasms, and can be found sometimes in mesenchymal tumors and nasopharyngeal carcinoma [21,22]. For serum sCD30 levels, high levels have been reported in different neoplasms (HL, ALCL, nasopharyngeal carcinoma, embryonal carcinoma of the testis) characterized by strong T-cell or B-cell activation [23]. In this study we reported that there was a significant correlation between both high CD30 expression and elevated sCD30 and WBCs count, BM blasts, adverse risk cytogenetics, FLT3/ITD mutation (That in contrast to Zheng W et al that found that CD30 expression did not associate with NPM1, FLT3 ITD, D835, or RAS mutation state [24].…”
Section: Discussionmentioning
confidence: 99%
“…CD30 is expressed abundantly on RS cells of HL, and in other numerous lymphoid malignancies of B-, T-, and natural killer (NK)-cell origin (Deutsch et al, 2011). Regarding its biological activity CD30 has pleiotropic biologic functions, being capable of promoting cell proliferation and survival as well as inducing antiproliferative responses and cell death.…”
Section: Modern Therapeutic Approaches Targeting the Tumor Microenvirmentioning
confidence: 99%
“…Regarding its biological activity CD30 has pleiotropic biologic functions, being capable of promoting cell proliferation and survival as well as inducing antiproliferative responses and cell death. Final effects of CD30 activation seem largely dependent on the microenvironment context (Deutsch et al, 2011). Unconjugated anti-CD30 antibodies have been tested in phase I and II studies showing limited clinical activity (Kasamon & Ambinder, 2008).…”
Section: Modern Therapeutic Approaches Targeting the Tumor Microenvirmentioning
confidence: 99%
“…overexpressed by anaplastic large-cell and Hodgkin lymphoma. 38 Contrarily to previous CD30-targeting approaches, brentuximab vedotin was found to induce durable objective responses and resulted in tumor regression in most patients with relapsed or refractory CD30-positive lymphomas. 39 Today, brentuximab vedotin is being investigated in patients at high risk of residual Hodgkin lymphoma following stem cell transplant ( Table 3, NCT01100502).…”
Section: Monoclonal Antibodies Under Advanced (Phase Iii-iv) Clinicalmentioning
confidence: 99%